73 Extreme risk protection orders in Washington: a statewide study. (5th May 2020) - Rowhani-Rahbar, Ali
Abstract : Statement of Purpose: Extreme Risk Protection Orders (ERPOs) restrict an individual's access to firearms if they pose a danger to themselves or others. We conducted a statewide study to examine the current uptake of this law and describe characteristics of petitioners and respondents. Approach: We requested all ERPO records from Washington Administrative Office of the Courts since the law implementation on January 1, 2017 to May 15, 2019. We traveled to county courthouses throughout the state to extract further information from each case file. Results: 243 ERPOs for 239 respondents were filed. There was wide variation in the rate of filing ERPOs by county ranging from 0 (in 16 counties) to 22 cases per 100, 000 population. County-level correlation between ERPO filing and firearm violent death rates was weak (correlation coefficient=0.18; p=0.45). 81% of respondents were male and 86% of petitioners were law enforcement agents. The ERPO filing reason was potential for harm to self (28%), others (36%), or both self and others (35%). 11% of petitions were denied or dismissed. 39% of respondents had unlawfully or recklessly used, displayed, or brandished a firearm (39%), 36% had expressed an intent to obtain a firearm, 12% had recently acquired a firearm, and 10% had access to someone else's firearm. Several respondents had a documented history of mental or behavioral health issues (40%), substance abuse (35%), and criminal behavior (30%). 614 firearms including 316 handguns and 298 long-guns were removed from 161 respondents. Conclusions: ERPOs are predominantly petitioned by law enforcement. We need to promote education and awareness on the purpose and process of filing ERPOs to increase their utilization. Significance: ERPOs can create safer circumstances for both petitioners and respondents by removing firearms from high-risk situations and engaging resources to provide treatment or address the underlying causes of the dangerous behaviors.